PERAN APLIKASI SISTEM KEUANGAN DESA (SISKEUDES) DALAM AKUNTABILITAS DANA DESA DAN KINERJA APARATUR DI DESA TULUNGREJO - Anggraeni, Novita; Yudiantoro, Deny (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.11.NO.05.TAHUN.2022DO - 10.24843/EEB.2022.v11.i05.p12, 2022)
The realization of accountability and growing public trust in the government's financial performance has now become an important issue in regional financial management. This study aims to determine the role of the village financial system application (Siskeudes) in village fund accountability and apparatus performance in Tulungrejo Village. This research is a qualitative type with data sources obtained directly through field observations and interviews with relevant sources at the Tulungrejo Village Head Office. The results of the study found that the implementation of Siskeudes in Tulungrejo Village was not optimal because human resources in this case village employees had not mastered the system well so that it had an impact on employee performance. It is known that the maximum system implementation will facilitate employee performance and improve employee performance results. Therefore, it is recommended that the local government in evaluating the implementation of this system be given training and assistance so that it will make it easier for employees to understand the performance of this system.